Invasive pest and diseases in Indian agriculture: Management and case studies - Kaur, Manjot; Bhullar, Muskan; Kaur, Ramneek (Review of Plant Studies, 2025)
Alien invasive insect pests threaten global food security, ecosystems, human health, and economies, with their introduction becoming inevitable amid globalization and liberalized trade. India has experienced a sharp rise in such invasions, from 10 recorded pests over a century (1889–1989) to over 15 in the last decade (2013–2023), exacerbated by the absence of natural enemies and delayed management. This paper critically reviews the status, entry pathways, and impacts of invasive pests in India, evaluates regulatory frameworks, and proposes strategic management measures. The study synthesizes documented evidence of recent invasions, including the Cassava Mealybug, Fall Armyworm, and South American Tomato Pinworm, alongside new alerts like the Apple Leaf Blotch Miner and Mango Soft Scale. Findings reveal that India’s porous borders, diverse agro-climates, and crop vulnerabilities facilitate pest establishment, leading to severe agricultural losses. Despite existing regulations, enforcement gaps, and rapid trade increases hinder effective containment. The paper highlights the urgent need for enhanced surveillance, early detection systems, and integrated pest management (IPM) strategies. Practical implications include strengthening phytosanitary measures, fostering international collaboration, and promoting research on biological control agents. By addressing regulatory weaknesses and adopting proactive mitigation approaches, India can reduce the ecological and economic risks posed by invasive pests, safeguarding its agrarian economy and global trade interests.